Research progress of rebound pain after nerve block in arthroscopic rotator cuff repair - Yang, Xue; Yang, Yujiao; Qin, Sulan; Chen, Yunliang (Frontiers in Medicine, 2025)
Arthroscopic rotator cuff repair (ARCR) is a commonly performed surgical intervention for rotator cuff injuries. The advent of ultrasound guidance has facilitated the widespread adoption of nerve blocks as an adjunct anesthetic and analgesic strategy in the perioperative phase of ARCR, offering notable benefits in maintaining patients' intraoperative hemodynamic stability and reducing opioid consumption. Despite the minimally invasive nature of ARCR, a subset of patients still experiences substantial pain, encompassing both acute pain and rebound pain following nerve block. Post-nerve block rebound pain is characterized by severe and disabling discomfort, which adversely impacts the patient experience and postoperative recovery. The mechanism underlying rebound pain after nerve block may involve aberrant excitation of relevant nerve fibers, the pharmacology of local anesthetics, nerve injury, local inflammatory factors, surgical anesthesia, and patient-specific variability. The review suggests that the incidence of post-nerve block rebound pain can be reduced, and postoperative pain management outcomes following ARCR can be improved, through interventions such as continuous nerve block, combined peripheral nerve block, administration of local anesthetic adjuvants, multimodal analgesia, and patient education.